RESPON PERTUMBUHAN BIBIT KAKAO PADA MEDIA SUBSOIL ULTISOL DENGAN PEMBERIAN PUPUK HAYATIBIOKOM DAN KOMPOS TTKS - Welly Jenny Hutagalung; Balonggu Siagian; Sanggam Silitonga Sanggam Silitonga (Jurnal Agroekoteknologi, 2013)
The effect of Planting Media Compound  and Biokom biofertilizer to Growth of   Cacao (Theobroma cacao L.) in Nursery, supervised by Ir. BALONGGU SIAGIAN MS dan Ir SANGGAM SILITONGA. The design of the experiment was randomized block design arranged in factorial with two factors. The first factor was planting media, 100% Subsoil Ultisol + 0% EOPB Compost, 75% Subsoil Ultisol + 25% EOPB Compost, 50% Subsoil Ultisol + 50% EOPB Compost, 25% Subsoil Ultisol + 75% EOPB Compost. The second factor is Biokom biofertilizer, 0 g/polibag, 3 g/polibag, 6 g/polibag, 9 g/polibag. The Parameter observed includes plant height (cm), number leafs (sheet), diameter of stem (mm), total of broad leaf (cm2), fresh and dry weight of crown (g) fresh and dry weight of root (g). The result of research showed that planting media influential significantly to plant height 12 and 14 weeks after planted, number leafs 8, 10, 12, 14 weeks after planted, diameter of stem 8, 10, 12, 14 weeks after planted, fresh and  dryweight of crown. Present of manure in fluential not significantly on plant height, number of leafs ,diameter of stem, total of broad leaf, fresh and  dryweight of crown and freshweight of root. Interaction between planting media and present of fertilizer influential not significantly on plant height, number of leafs ,diameter of stem, total of broad leaf, fresh and  dryweight of crown and freshweight of root.   Key Words : Empty Oil Palm Bunch (EOPB) Compost, Biokom Biofertilizer, Cacao, Nursery